Strategies, challenges, and outcomes of heat stress resilience in sub-Saharan African community-based cattle feedlots: a systematic review - Slayi, Mhlangabezi; Zhou, Leocadia; Jaja, Ishmael Festus (Frontiers in Veterinary Science, 2024)
In sub-Saharan Africa, cattle feedlots face a significant challenge in dealing with heat stress. However, there is a lack of inclusive strategies for resilience in these situations. The aim of this systematic review is to investigate the strategies, challenges, and outcomes related to heat stress resilience in community-based cattle feedlots in sub-Saharan Africa. The PRISMA approach, which is a method for reporting systematic reviews and meta-analyses, was used to identify, screen, and analyze 30 peer-reviewed articles published over the last 20 years from Google Scholar and Scopus. The review found that key strategies to mitigate heat stress include providing shade through natural and artificial means, ensuring constant access to cool, clean water using water spraying systems and cooling ponds, and implementing nutritional adjustments such as high-energy feeds and electrolyte supplements. Additionally, genetic selection for heat-tolerant breeds and management practices like adjusting feeding times and improving ventilation were found to be effective in dealing with heat stress. In particular, local germplasm and genetic traits of cattle in sub-Saharan Africa play a crucial role in heat stress resilience. Indigenous breeds, which have adapted to the region’s harsh climate over centuries, exhibit traits such as higher heat tolerance, better water-use efficiency, and improved feed conversion rates under heat stress conditions. This genetic resilience can be enhanced through targeted breeding programs aimed at amplifying these beneficial traits. Implementing these strategies resulted in improved cattle health and productivity, as evidenced by enhanced weight gain, better reproductive performance, and lower mortality rates. The socio-economic benefits of these strategies included reduced economic losses and increased farmer incomes, which in turn contributed to improved community health and nutrition. However, the review also identified significant challenges, including financial constraints, limited access to knowledge and training, and cultural resistance. To address these barriers, the review recommends increased investment in affordable cooling technologies, farmer education, and community-based initiatives. Additionally, leveraging the genetic strengths of local cattle breeds should be prioritized to maximize the effectiveness of heat stress resilience strategies.